Bile Acid Binding Resin Improves Metabolic Control through the Induction of Energy Expenditure - Watanabe, Mitsuhiro (Public Library of Science, 2012)
BACKGROUND: Besides well-established roles of bile acids (BA) in dietary lipid absorption and cholesterol homeostasis, it has recently become clear that BA is also a biological signaling molecule. We have shown that strategies aimed at activating TGR5 by increasing the BA pool size with BA administration may constitute a significant therapeutic advance to combat the metabolic syndrome and suggest that such strategies are worth testing in a clinical setting. Bile acid binding resin (BABR) is known not only to reduce serum cholesterol levels but also to improve glucose tolerance and insulin resistance in animal models and humans. However, the mechanisms by which BABR affects glucose homeostasis have not been established. We investigated how BABR affects glycemic control in diet-induced obesity models. METHODS AND FINDINGS: We evaluated the metabolic effect of BABR by administrating colestimide to animal models for the metabolic syndrome. Administration of BABR increased energy expenditure, translating into significant weight reduction and insulin sensitization. The metabolic effects of BABR coincide with activation of cholesterol and BA synthesis in liver and thermogenesis in brown adipose tissue. Interestingly, these effects of BABR occur despite normal food intake and triglyceride absorption. Administration of BABR and BA had similar effects on BA composition and thermogenesis, suggesting that they both are mediated via TGR5 activation. CONCLUSION: Our data hence suggest that BABR could be useful for the management of the impaired glucose tolerance of the metabolic syndrome, since they not only lower cholesterol levels, but also reduce obesity and improve insulin resistance.